2021
DOI: 10.5812/ijpr.123828
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Wound Fluid on Breast Cancer-derived Spheroids in a 3D Culture System: A Case Series Study

Abstract: : Surgery is the standard treatment for breast malignancies, although local and distant relapses might occur. Previous studies have shown that surgery-induced wound fluid (WF) contains tumor-initiating and progressing factors; however, these experiments have only been performed on breast cancer cell lines. Since a cancerous tumor includes various components like malignant cells, recruited non-malignant cells and extracellular matrix, those investigations that only focused on cancer cell lines themselves are no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…Interestingly, one sample displayed the opposite result. We concluded that, however, most BC patients take advantage of removing seroma, the effects of seroma on tumor progression may not show a similar effect in all patients, and it can depend on many unknown factors ( 126 ). In another study, we assessed the radiobiological impact of IORT-seroma on human-derived specimens in a 3D model mentioned above.…”
Section: Introductionmentioning
confidence: 94%
“…Interestingly, one sample displayed the opposite result. We concluded that, however, most BC patients take advantage of removing seroma, the effects of seroma on tumor progression may not show a similar effect in all patients, and it can depend on many unknown factors ( 126 ). In another study, we assessed the radiobiological impact of IORT-seroma on human-derived specimens in a 3D model mentioned above.…”
Section: Introductionmentioning
confidence: 94%